A gift before dying : a novel - Kempt, Malcolm (Crown, 2026)
"In a gripping and hauntingly atmospheric novel set against the unforgiving landscape of the Arctic Circle, a disgraced police investigator discovers that his path to redemption is paved with ice-and blood"-- Provided by publisher.